Comparison of the Efficacy of Low-Level Laser Therapy and Pulsed Ultrasound Treatment in Carpal Tunnel Syndrome: A Placebo-Controlled Study - DURUÖZ, MEHMET TUNCAY (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2013)
Objective: To evaluate the effect of low-level laser treatment (LLLT) and pulsed ultrasound (US) treatment in carpal tunnel syndrome (CTS) and to compare the effects of both treatment modalities. Materials and Methods: 60 patients diagnosed with CTS were randomly divided into four groups as US group (group 1), placebo US group (group 2), LLLT group (group 3) and plasebo LLLT group (group 4). Both treatments were applied five days a week for three weeks. Clinical and electrophysiological assessments were performed before and 3, 6 and 12 months after treatment. Pain, hypoesthesia and handgrip strength were evaluated. The Boston Questionnaire was used to assess the severity of symptoms and functional status. Results: 52 patients with 101 hands completed the study. Demographic and electrophysiological parameters were similar in the four groups. Both pulsed US treatment and LLLT were found to provide significant improvements in clinical parameters such as pain, sensory loss, symptom severity score and functional capacity score (p<0.05). No significant beneficial effect was observed in both placebo groups (p<0.05). Evaluations of the electrophysiological parameters showed no significant difference between the groups (p>0.05). In terms of clinical efficacy, pulsed US was found to be superior to LLLT (p<0.05). Conclusion: The two treatment modalities showed significant improvements in subjective clinical symptoms while no significant changes were observed in any electrophysiological parameters.
Keywords: Carpal tunnel syndrome; low-level laser; pulsed ultrasound; treatment; placebo; SOFT-TISSUE LESIONS; CONTROLLED-TRIAL; IRRADIATION; PAIN; SYMPTOMS